Spectral Results for Operator Valued Functions - Reddy, B. Surender; Dharmaiah, V. (Journal of Informatics and Mathematical Sciences, 2010)
In this paper, the general spectral results of operator valued functions in particular holomorphic operator valued functions and operator polynomials are studied. Further the completeness results of quadratic operator polynomials are presented.